Didática histórico-crítica na Educação Infantil: do aprender a aprender ao ensino aprendizagem desenvolvente - Ribeiro, Kethlen Vasconcelos (Brasil, 2024)
The article aims to reflect on the contributions of Historical-Critical Pedagogy to thinking about didactics in Early Childhood Education, more precisely, in pre-school. It starts from the understanding that it is necessary to know the philosophical and psychological bases of Historical-Critical Pedagogy and how these support a transformative pedagogy through critical and propositional didactics, which articulates and mobilizes alternative content and practices to hegemonic pedagogies. The teacher's teaching, aimed at the development of the child as a social and cultural subject, is problematized and focused on the foundations of the theory of periodization of psychic development and the assumptions of historical-dialectical materialism. The study results from bibliographical research, supported by specialized literature, whose main theoretical-conceptual contributions focus on Historical-Critical Pedagogy and the Theory of Periodization of Psychic Development formulated within the scope of Historical-Cultural Theory. The results point to an early childhood education in which teaching is structuring of educational work with a view to the child's integral development, in which the experiences are linked to the guiding activity to provide the potential found in each child.